SOCIAL RESPONSIBILITY OF BUSINESS: MAIN COMPONENTS AND PRIORITY DIRECTIONS OF IMPLEMENTATION - PUCHKOVA, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the components and directions of the implementation of social responsibility of business, which are implemented under the influence of current events in Ukraine. Approaches to the definition of the concept of "social responsibility of business" according to scientists M. Friedman, G. Bowen, A. Carroll, from the position of the World Council of Entrepreneurs for Sustainable Development and the World Bank Institute are given. The relationship between social responsibility of business and sustainable development is indicated. Differences in the characteristics of social responsibility of business and philanthropy according to the criteria of involvement, purpose, participation in decision-making, strategicness and dependence on external circumstances are determined. It was established that the concept of social responsibility of business has a wider meaning than charity. Such key principles of social responsibility of business as openness, systematicity, reliability, regularity are indicated. The main components of internal and external social responsibility of business are revealed. The reasons that restrained the development of social responsibility of business in Ukraine are highlighted. The actions of the state regarding the activation of social responsibility in Ukraine are indicated. Measures have been taken by leading business structures regarding social responsibility at the beginning of hostilities in Ukraine in such areas as humanitarian aid to the population, support of medical facilities, evacuation and accommodation of the population from the areas of hostilities, organization of shelters for the population. The five-component model of social responsibility of business in war conditions is given and characterized according to the following components: business continuity, people's safety, army assistance, partnership, local communities. Referred to the results of the study of the sustainability of Ukrainian business during the war. Attention was focused on the following key directions of the SVB: systematization and coordination of corporate volunteering within the organization, the application of the practice of well-being (corporate well-being) and war/work balance (balancing work during the war) and Ukraine first, National Identity, Ukraine Culture Code.
Keywords: sustainable development; social responsibility of business; charity; model of social responsibility; business ethics; martial law conditions